AN ANALYSIS LOANWORD USED IN EDUCATION OF COMPAS DAILY NEWSPAPER - Putri, D.ivi Marliliyan; Istiqomah, Ros Suciati (PROJECT (Professional Journal of English Education), 2019)
The objectives of the research are to know how many types loanword and the most dominant loanword in compass daily news paper. The method used in this research is qualitative method to get specific data. The subjects of this research is  from compass news paper 2nd about education of april 2019. The data are collected and categoried based on loanword.  The result showed there are three types of loanword in the compas news paper, they are loanword that has been calculated there are loanword with complete phonetic substitution with the result percentage is 9,92%, rather then loanword without phonetic substitution is 1,18%, and loanword patial phonetic subtituion is 4,01%. Besides, the most dominant loanword used type loanword with complete phonetic substitution